New studies in textual interplay - Evans, Craig A.; Oropeza, Brisio J.; Sloan, Paul T. (Library of New Testament studies, 2022)
"This volume features a body of work selected by Craig A. Evans, B. J. Oropeza, and Paul T. Sloan, designed to examine just what is meant by 'intertextuality,' including metalepsis and the controversial and exciting approach known as 'mimesis.' Beginning with an introduction from Oropeza which orients readers in a complex and evolving field, the contributors first establish the growing research surrounding the discipline, before examining important texts and themes in the New Testament Gospels and epistles"--